Convergent Loss of Chemoreceptors across Independent Origins of Slave-Making in Ants. (20th October 2021) - Jongepier, Evelien; Séguret, Alice; Labutin, Anton; Feldmeyer, Barbara; Gstöttl, Claudia; Foitzik, Susanne; Heinze, Jürgen; Bornberg-Bauer, Erich
Abstract: The evolution of an obligate parasitic lifestyle often leads to the reduction of morphological and physiological traits, which may be accompanied by loss of genes and functions. Slave-making ants are social parasites that exploit the work force of closely related ant species for social behaviors such as brood care and foraging. Recent divergence between these social parasites and their hosts enables comparative studies of gene family evolution. We sequenced the genomes of eight ant species, representing three independent origins of ant slavery. During the evolution of eusociality, chemoreceptor genes multiplied due to the importance of chemical communication in insect societies. We investigated the evolutionary fate of these chemoreceptors and found that slave-making ant genomes harbored only half as many gustatory receptors as their hosts', potentially mirroring the outsourcing of foraging tasks to host workers. In addition, parasites had fewer odorant receptors and their loss shows striking patterns of convergence across independent origins of parasitism, in particular in orthologs often implicated in sociality like the 9-exon odorant receptors. These convergent losses represent a rare case of convergent molecular evolution at the level of individual genes. Thus, evolution can operate in a way that is both repeatable and reversible when independent ant lineages lose important social traits during the transition to a parasitic lifestyle.